Enhancer DNA methylation: implications for gene regulation. Issue 6 (24th September 2019) - Angeloni, Allegra; Bogdanovic, Ozren
Abstract: DNA methylation involves the addition of a methyl group to the fifth carbon of the pyrimidine cytosine ring (5-methylcytosine, 5mC). 5mC is widespread in vertebrate genomes where it is predominantly found within CpG dinucleotides. In mammals, 5mC participates in long-term silencing processes such as X-chromosome inactivation, genomic imprinting, somatic silencing of germline genes, and silencing of repetitive DNA elements. The evidence for 5mC as a dynamic gene-regulatory mechanism is mostly limited to specific examples, and is far from being completely understood. Recent work from diverse model systems suggests that 5mC might not always act as a dominant repressive mechanism and that hypermethylated promoters and enhancers can be permissive to transcription in vivo and in vitro . In this review, we discuss the links between 5mC and enhancer activity, and evaluate the role of this biochemical mechanism in various biological contexts.